pk002393: Revolutionary greetings from Ireland - Sands, Bobby; The Republican Movement
"Prentbriefkaart in zwart-wit voorstellend twee gemaskerde en gewapende mannen in het struikgewas. Tekst : There can never be peace in Ireland until the foreign, oppressive British presence is removed, leaving all the Irish peoples as a unit to control their own affairs and determine their own destinies as a sovereign people, free in mind and body, separate and distinct physically, culturally and economically. FULL TEXT AVAILABLE AT AMSAB-ISH"